(untitled) (MCIT: Proceedings of International scientific and practical conference, 2023)
A modern computer network counts tens of millions of servers and hundreds of millions of workstations. Network technologies have found widespread use in industry and business, so network reliability has become one of the most pressing problems. In general, the reliability of all systems is determined by the reliability of their constituent elements. Different elements have different reliability. In many cases, reliability and reliability distributions are determined empirically. If we define the reliability of the system as the possibility of communication between different nodes and workstations, then the reliability of the Internet turns out to be equal to the whole. Unless your workstation is among thousands of nodes, you cannot guarantee the absolute reliability of the network, so it is clear that both definitions are completely unacceptable. The selection of criteria for determining the reliability and performance of information computer networks is one of the main problems of information systems